2017
DOI: 10.1111/ijcs.12405
|View full text |Cite
|
Sign up to set email alerts
|

Individual choice or collective action? Exploring consumer motives for participating in alternative food networks

Abstract: Alternative food networks (AFNs) are growing in number and relevance in Germany. Those networks include new models of production and distribution, such as food cooperatives (FoodCoops), self-harvest gardens or community-supported agriculture (CSA) schemes. AFNs, as an alternative to conventional food supply systems, are characterized by a close producer-consumer interaction.They are typically located within urban or peri-urban areas. The study aims to identify the rationale and motivation of urban residents in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 34 publications
4
80
0
6
Order By: Relevance
“…From an advocacy perspective, this ability to change society may be limited if farmers’ messages are ambiguous or infrequent. This finding echoes other research that shows that alternative food networks lack a consistent and unified voice that would be necessary to create widespread change (Zoll et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…From an advocacy perspective, this ability to change society may be limited if farmers’ messages are ambiguous or infrequent. This finding echoes other research that shows that alternative food networks lack a consistent and unified voice that would be necessary to create widespread change (Zoll et al, ).…”
Section: Discussionsupporting
confidence: 83%
“…In comparison, urban agriculture in developed countries is undertaken for subsistence purposes (cost saving) but more commonly for psychological and personal factors such as the desire for high-quality food (fresh, convenient, organic, better tasting), previous exposure, health reasons (mental and physical), as well as political and environmental convictions (such as sustainability issues) [43,[93][94][95]. This discrepancy in motivations is partially driven by differing perspectives and experiences of nature, foodscapes and food security.…”
Section: Urban Agriculture's Role In Food Securitymentioning
confidence: 99%
“…Local food can help give back communities that ability to control, understand and influence the food they eat [63]. This awareness is resulting in an influx of food sovereignty research and movements worldwide [36,93,98], which could have significant implications for the wider food system and political governance in the future. Learning from developed countries, preventative policy should be made a priority in low-income countries that are currently undergoing urban population influx and transitioning away from local food production (with shorter supply chains) towards a more globalised food system.…”
Section: Urban Agriculture's Role In Food Securitymentioning
confidence: 99%
“…Goetzke, Nitzko, and Spiller () studied the relationship between different domains of well‐being and organic/functional food consumption and concluded that alternative medication and spirituality, social community involvement, physical activity and healthy eating have a positive impact on organic food eating. A recent study on German AFNs (Zoll et al, ) revealed that the attitudes of the participants are often mixed and can vary over a broad range and that well‐being components, to different degrees, are also part of the motives of AFN participants. In relation to AFNs and organic food consumption, Som Castellano () described the impact of AFNs on the popularity of organic and local food and recognized their contribution to environmental and community well‐being.…”
Section: Theoretical Partmentioning
confidence: 99%